Mediating Effects of Insecure Parental Attachment on the Relationship Between Direct and Vicarious Family Victimization and Child-to-Parent Violence - Navas-Martínez, María J.; León, Samuel P.; Cano-Lozano, M. Carmen (Journal of family violence, 2025)
Purpose Family victimization has been consistently identified as one of the most relevant predictors of child-to-parent violence (CPV). However, studies focused on examining the mechanisms through which family victimization could exercise influence on CPV are still scarce. The main objective was to analyze whether insecure parental attachment (preoccupied, avoidant, and traumatized) mediates the relationship between family victimization (direct and vicarious) and CPV (toward fathers and mothers). Methods A total of 1,514 Spanish university students (51% boys) between 18 and 25 years old ( M age = 20.7, SD = 1.9) who retrospectively described their experiences between the ages of 12 and 17 years old participated. Results The results showed significant and positive relationships between CPV, direct and vicarious family victimization, and insecure parental attachment styles. More relevant, insecure attachment partially mediated the relationship between direct victimization and CPV, whereas the mediation effect was total in the relationship between vicarious victimization and CPV. Specifically, traumatized attachment stands out as the attachment style that is implicated in the relationship between family victimization and violence toward both fathers and mothers. Conclusions The findings suggest that family victimization experiences could have an impact on the establishment of negative emotional bonds which in turn could contribute to the development of CPV. Research and professional practical implications are discussed, highlighting attachment's role as a valuable intervention and prevention tool given its dynamic nature.